OZONE IMPROVES AUTOGENOUS GRAFT HEALING IN EXPERIMENTAL DIABETES MELLITUS: A MORPHOMETRIC AND IMMUNOHISTOCHEMICAL STUDY - Aysan Lektemür Alpan; Hülya Toker; Hatice Özer (Selçuk University, 2020)
Backround: Diabetes mellitus (DM) is a metabolic disorder which plays crucial role in the pathogenesis of periodontitis. Ozone have several actions such as antimicrobial ,immunostimulating, antihypoxic effects, and activates antioxidant enzymes and angiogenesisAim: The aim of this study is to investigate the effect of gaseous ozone on bone healing in diabetic rat calvarial defects treated with autogenous bone graft, morphometrically and immunohistochemically.Material and Methods: Diabetes was induced and critical size defects were created on rats. Study groups: 1-Empty defect (Control, n=14) group, 2-Autograft (AG, n=14) group, 3-Empty defect+ozone therapy (Control+Ozone, n=14) group, 4-Autograft+ozone application (AG+Ozone, n=14) group. Gaseous ozone was applied on the operation day and the following 2 weeks daily (140ppm @ 2L/d, 2.24 mg). Total bone area was measured. Osteocalcin and Bone morphogenic protein-2  protein expressions were evaluated.Results: Control and Control+Ozone groups had no osteoclast and residuel lacunae during the study . Osteoblasts in AG+Ozone group were higher than AG group at 4th week (p>0.05). AG+Ozone group had more total bone area than AG group at 4th week. AG+Ozone group revealed more BMP-2 immune positivity compared to the other groups. Osteocalcin immune positivity in AG groups was higher than those of the Control groups.Conclusion: Within the limitations of this study, gaseous ozone application decreased osteoclast number and increased osteoblast number and bone regeneration, especially, in early stages of bone regeneration in diabetic rats. KEYWORDS: autograft, bone regeneration, calvarial defect, experimental diabetes mellitus, ozone